Hypofibrinogenemia induced by tigecycline: a potentially life-threatening coagulation disorder. Issue 10 (October 2015) - Sabanis, Nikolaos; Paschou, Eleni; Gavriilaki, Eleni; Kalaitzoglou, Asterios; Vasileiou, Sotirios
Abstract: A 74-year-old female patient with end-stage renal disease, undergoing periodic hemodialysis, was hospitalized due to infection by multidrug-resistant Acinetobacter baumannii after hip replacement surgery. She was treated with tigecycline, a glycylcycline agent. Subsequently she developed coagulation disorders as substantiated by increased international normalized ratio (INR), prolonged partial thromboplastin time (aPTT), and severe hypofibrinogenemia, followed by transaminasemia, cholestasis, and anemia. Ultrasonography and computed tomography revealed no underlying pathological entities. Tigecycline was discontinued and the patient underwent daily hemodialysis and received multiple fresh frozen plasma transfusions. Additionally, she was treated with colistin. Her clinical and laboratory status improved. We suggest that patients treated with tigecycline should be monitored for changes in INR, aPTT, and fibrinogen levels to avoid severe, life-threatening coagulation disturbances.